Petri Nets as Models of Linear Logic - Engberg, Uffe; Winskel, Glynn (DAIMI Report Series, 1990)
The chief purpose of this paper is to appraise the feasibility of Girad’s linear logic as a specification language for parallel processes. To this end we propose an interpretation of linear logic in Petri nets, with respect to which we investigate the expressive power of the logic.